2007
DOI: 10.1177/0093854806295859
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Megargee's Criminal Offender Infrequency (Fc) Scale in Detecting Malingering Among Forensic Examinees

Abstract: E. I. Megargee (2004) developed a Minnesota Multiphasic Personality Inventory (MMPI-2) Infrequency scale for use in criminal settings called the Criminal Offender Infrequency (Fc) scale. This study compared Fc with 7 other MMPI-2 validity scales in detecting malingering by obtaining archival data from evaluations of male inmates that used the MMPI-2 and the Structured Interview of Reported Symptoms (SIRS). Participants were placed into groups based on the SIRS results: feigning, honest, or indeterminate. Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…1. The SIRS was only administered to participants in the Gassen, Pietz, Spray, and Denney (2007) study when malingering was suspected due to validity scale elevations on the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). The results of their study should therefore be interpreted with caution.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…1. The SIRS was only administered to participants in the Gassen, Pietz, Spray, and Denney (2007) study when malingering was suspected due to validity scale elevations on the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). The results of their study should therefore be interpreted with caution.…”
Section: Notementioning
confidence: 99%
“…Lewis, Simcox, and Berry (2002) recently found F b (Back Infrequency Scale) to have the highest hit rate of the F scale family in detecting malingerers as classified by the structured interview of reported symptoms (SIRS; Rogers, 1986). Also, recent findings suggest that the criminal offender infrequency (F c ) scale has significant predictive utility in detecting malingerers as defined by the SIRS (Gassen, Pietz, Spray, & Denney, 2007). 1 Before measures of malingering can be accepted as valid, the generalizability of the results of simulation studies to actual forensic populations must be demonstrated.…”
mentioning
confidence: 99%
“…Although they represent the standard in cognitive malingering research, studies utilizing a known-groups design (i.e., defining symptom-overreporting groups based on an empirically validated response bias criterion) are scarce with regard to feigned psychopathology and are sometimes confounded by methodological concerns. For example, Gassen, Pietz, Spray, and Denney (2007) found Megargee’s (2004) Criminal Offender Infrequency (Fc) scale produced the highest hit rate of any MMPI–2 validity scale in detecting criminal defendants who were classified as malingering by the Structured Interview of Reported Symptoms (SIRS; Rogers, Bagby, & Dickens, 1992). However, it is difficult to determine how to interpret these results, as defendants were only administered the SIRS if the evaluating clinician determined that their MMPI–2 results were indicative of symptom feigning.…”
mentioning
confidence: 99%
“…En primer lugar, observamos que en unos estudios (Arbisi y Ben-Porath, 1998;Hahn, 2005;Wetter, Baer, Berry, Smith, y Larsen, 1992) se instruyó a los sujetos experimentales las instrucciones dadas a los sujetos experimentales que fingieran sintomatología muy grave y sin instruirlos en que podrían ser detectados por escalas, buscando de este modo una simulación extrema en la que este tipo de medidas son las efectivas. En segundo lugar, advertimos que la causa de los tamaños del efecto exageradamente elevados que habían encontrado descansaba en el grupo de contraste que no era ni de población general ni la población normativa, sino la penitenciaria (Gassen, Pietz, Spray, y Denney, 2007;Kurtz, 1992;Vaughan, 1995) o la psiquiátrica (Mihura et al, 2000). Por tanto, en estos estudios no se mide propiamente la simulación al no comprarse las respuestas simuladas con respuestas bajo instrucciones estándar de población normal.…”
Section: Estudio De Los Outliersunclassified